2020
DOI: 10.1002/aenm.201904013
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Exciton Dissociation at Organic Semiconductor Interfaces Facilitated by the Orientation of the Delocalized Electron–Hole Wavefunction

Abstract: In organic semiconductors, optical excitation does not necessarily produce free carriers. Very often, electron and hole are bound together to form an exciton. Releasing free carriers from the exciton is essential for the functioning of photovoltaics and optoelectronic devices, but it is a bottleneck process because of the high exciton binding energy. Inefficient exciton dissociation can limit the efficiency of organic photovoltaics. Here, nanoscale features that can allow the free carrier generation to occur s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 69 publications
7
57
1
Order By: Relevance
“…where the first term represents for the change in Coulomb binding energy, and the second term represents for the entropy driving force for CT exciton dissociation. [27][28][29][30] Here, W represents for the electronic degeneracy, that is, the molecular states available to accommodate electrons and holes (DOS FL ); ε 0 and ε r are the vacuum permittivity and the relative dielectric constant respectively; and r is the initial electron-hole distance of the CT exciton. For doped heterojunction, we estimate the local carrier density to be ≈5 × 10 16 cm −3 using simple parallel capacitor model (with ΔE = 80 mV as indicated in Figure 1e,f).…”
Section: (7 Of 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…where the first term represents for the change in Coulomb binding energy, and the second term represents for the entropy driving force for CT exciton dissociation. [27][28][29][30] Here, W represents for the electronic degeneracy, that is, the molecular states available to accommodate electrons and holes (DOS FL ); ε 0 and ε r are the vacuum permittivity and the relative dielectric constant respectively; and r is the initial electron-hole distance of the CT exciton. For doped heterojunction, we estimate the local carrier density to be ≈5 × 10 16 cm −3 using simple parallel capacitor model (with ΔE = 80 mV as indicated in Figure 1e,f).…”
Section: (7 Of 11)mentioning
confidence: 99%
“…Larger entropy means more states for carriers to stay, which reduces the free energy of CT-CS transition according to Gibbs equation. [27][28][29][30] Previous studies have shown that all abovementioned properties are closely related to the local morphology of crystallinity, mixing ratio, and molecular orientation at the D/A heterojunction. [31][32][33][34] The complexity in local morphology regulation and characterization hinders the rational optimization of heterojunction properties in OPVs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the electrons and holes combine to generate excitons in EML under the action of coulomb static electricity [ 63 , 64 ]. As the excitons are excited, they need to release energy in some way and return to the ground state [ 65 , 66 ]. There are two main ways to release energy: one is in the form of light radiation, and the other is in the form of non-radiation [ 67 ].…”
Section: Introduction To Oledmentioning
confidence: 99%
“…The dissociation mechanisms of interfacial CT excitons, having binding energies ∼10 times higher than ambient thermal energies 1,15 , are also currently in discussion. Several physical effects can impact the exciton dissociation dynamics, such as entropy 6,[17][18][19] , vibronic couplings [19][20][21][22] , energy offset 5,[22][23][24][25][26][27][28][29][30][31] , disorder [32][33][34][35][36] , hybridization between CT and localized states 7,22,[37][38][39] , and also electronic delocalization and polarization 14,34,[40][41][42][43][44][45][46][47][48][49][50] , among others.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have addressed the microscopic structures of the DA interfaces and their impact on free-carrier-generation [5][6][7]34,38,46,47,[51][52][53][54] . While atomistic simulations can provide invaluable mechanistic and structure-property insights, the importance of going beyond minimal (bimolecular) interface models has been emphasized 34,47,52,54 .…”
Section: Introductionmentioning
confidence: 99%